Impact of Video Content and Technical Specifications on Subjective Quality Assessment - Pauliks, R.; Slaidins, I. (Elektronika ir Elektrotechnika, 2012)
Replacement of traditional analog TV broadcasting services with various video services based on new advanced digital technologies not always provide high quality of video image if evaluated by viewer. This paper presents an analysis of impact of the video content and technical specifications on the subjective assessment of video picture quality made by non-expert observers. The measurements are performed in experimental setup with 25 observers, using 11 video scenes with wide range of technical specification, various analog and digital interfaces. The results show that high definition analog and digital video interfaces are evaluated by observers as providing nearly the same quality, but temporal activity in a video scene had a significant effect on the subjective quality assessment score. For a very vibrant video scenes with a high level values of temporal and spatial activity there is no significant difference in subjective quality assessment score either using standard definition or high definition, analog or digital interface. Ill. 3, bibl. 20, tabl. 5 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.122.6.1828